An accurate, precise method for general labeling of extracellular vesicles - Gray, Warren D. (MethodsX, 2015)
Extracellular, membrane vesicles (microvesicles, exosomes) are secreted by cells and may serve as mediators of intercellular communication. Methods for detecting them by flow cytometry have included the use of agents that fluorescently stain vesicle membrane, or fluorescent antibodies that target specific cell-of-origin antigens. However, these methods may falsely detect cell debris or require prior cell-of-origin knowledge. Here, we demonstrate the suitability of calcein AM for detection of intact extracellular vesicles (EVs) by flow cytometry. • Calcein AM is non-fluorescent until it passively enters EVs, after which it is activated and becomes fluorescent and EV-impermeant. • Permeabilized/lysed EVs label positive with antibodies and lipophilic membrane stain, whereas no labeling was observed with calcein. In contrast to methods that use antibodies or membrane stains, calcein AM allows for the differentiation between intact EVs and debris. • Calcein AM can be used for detection of intact EVs from numerous cell types.